The Finger Dexterity Test: Validation study of a smartphone-based manual dexterity assessment - Van Laethem, Delphine; Denissen, Stijn; Costers, Lars; Descamps, Annabel; Baijot, Johan; Van Remoortel, Ann; Van Merhaegen-Wieleman, Annick; D'hooghe, Marie B; D'Haeseleer, Miguel; Smeets, Dirk; Sima, Diana M; Van Schependom, Jeroen; et al. (Multiple sclerosis, 2024)
The Nine-Hole Peg Test (9HPT) is the golden standard to measure manual dexterity in people with multiple sclerosis (MS). However, administration requires trained personnel and dedicated time during a clinical visit. The objective of this study is to validate a smartphone-based test for remote manual dexterity assessment, the ico Finger Dexterity Test (FDT), to be included into the ico application. A total of 65 MS and 81 healthy subjects were tested, and 20 healthy subjects were retested 2 weeks later. The FDT significantly correlated with the 9HPT (dominant: ρ = 0.62, < 0.001; non-dominant: ρ = 0.52, < 0.001). MS subjects had significantly higher FDT scores than healthy subjects (dominant: = 0.015; non-dominant: = 0.013), which was not the case for the 9HPT. A significant correlation with age (dominant: ρ = 0.46, < 0.001; non-dominant: ρ = 0.40, = 0.002), Expanded Disability Status Scale (EDSS, dominant: ρ = 0.36, = 0.005; non-dominant: ρ = 0.31, = 0.024), and disease duration for the non-dominant hand (ρ = 0.31, = 0.016) was observed. There was a good test-retest reliability in healthy subjects (dominant: = 0.69, = 0.001; non-dominant: r = 0.87, < 0.001). The ico FDT shows a moderate-to-good concurrent validity and test-retest reliability, differentiates between the MS subjects and healthy controls, and correlates with clinical parameters. This test can be implemented into routine MS care for remote follow-up of manual dexterity.